Russian Literary Politics and the Pushkin Celebration of 1880 - Levitt, Marcus C. (Book collections on Project MUSE., 1989)
In an event acknowledged to be a watershed in modern Russian cultural history, the elite of Russian intellectual life gathered in Moscow in 1880 to celebrate the dedication of a monument to the poet Alexander Pushkin ...